Culture and Language Maintenance Efforts of the Hungarian Community in San Diego - Forintos, Éva (FOCUS: Papers in English Literary and Cultural Studies, 2023)
In this paper, I argue that members of the Hungarian community (who are assumed to be first-generation Americans) living in the city of San Diego, California and have assimilated into the mainstream culture of their adopted country, have developed an identity that can be regarded as a combination of their native language and culture as well as their dominant language and culture. This distinctively dynamic identity contributes to the maintenance of their heritage language and culture. Through negotiating their identity via intentional code-mixing in their written discourse, they invite members of the mainstream group to learn about and become interested in their culture. Among the many types of significant influences that minority community media can have on ethnic identity construction, there is an opportunity for the community to be present inside and outside of the group as well as operating as an essential communicator of culture and a creator of cultural artifacts. The illustrative material analyzed in this paper is sourced from the House of Hungary (San Diego) website and the latest issues of their newsletter.